Impact of Conventional and Atypical MAPKs on the Development of Metabolic Diseases - Toufic Kassouf; Grzegorz Sumara (Biomolecules, 2020)
The family of mitogen-activated protein kinases (MAPKs) consists of fourteen members and has been implicated in regulation of virtually all cellular processes. MAPKs are divided into two groups, conventional and atypical MAPKs. Conventional MAPKs are further classified into four sub-families: extracellular signal-regulated kinases 1/2 (ERK1/2), c-Jun N-terminal kinase (JNK1, 2 and 3), p38 (α, β, γ, δ), and extracellular signal-regulated kinase 5 (ERK5). Four kinases, extracellular signal-regulated kinase 3, 4, and 7 (ERK3, 4 and 7) as well as Nemo-like kinase (NLK) build a group of atypical MAPKs, which are activated by different upstream mechanisms than conventional MAPKs. Early studies identified JNK1/2 and ERK1/2 as well as p38α as a central mediators of inflammation-evoked insulin resistance. These kinases have been also implicated in the development of obesity and diabetes. Recently, other members of conventional MAPKs emerged as important mediators of liver, skeletal muscle, adipose tissue, and pancreatic β-cell metabolism. Moreover, latest studies indicate that atypical members of MAPK family play a central role in the regulation of adipose tissue function. In this review, we summarize early studies on conventional MAPKs as well as recent findings implicating previously ignored members of the MAPK family. Finally, we discuss the therapeutic potential of drugs targeting specific members of the MAPK family.